Improving the Transparency of Data Access Conditions in the SSH Domain: Recommendations based on a small-scale analysis of the conditions applied to restricted access datasets - Deborah Thorpe; Ricarda Braukmann; Angelica Maineri (International Journal of Digital Curation)
The benefits of making data available for reuse are recognized by many. While some datasets can be openly available, others contain sensitive or personal data that needs to be protected. To allow the sharing of the latter datasets, many trustworthy digital repositories provide options to publish data restricted access. However, detailed standardized information about the access conditions for these restricted access datasets are often lacking from the metadata. Researchers interested in reusing these datasets can thus not judge whether they are eligible to reuse data and under what conditions.